2019
DOI: 10.3329/fmcj.v13i2.43644
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Vesicovaginal Fistula: Experience of 30 Cases and Analysis of Outcome Predictors

Abstract: Female genital fistula is a serious medical condition in which a perforation develops most commonly between bladder and vagina (VVF). Although the majority of genitourinary fistulas can be closed surgically, the successful closure depends on many factors. In this retrospective study, the records of 30 women with a mean age of 23.8 years were assessed; 13% of the VVF occurred after abdominal hysterectomy, 67% after Caesarean section, and 20% after difficult vaginal delivery. Six (20%) women had previous repair.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…13,21,36,46,47,[53][54][55] All retrospective nonrandomized comparative studies (30 studies) and prospective nonrandomized comparative studies (5 studies) were considered high risk of bias because these studies evaluated interventions designated by surgeon preference, varied in their follow-up, provided limited information on evaluation of cure, and did not control for confounding factors. 14,[16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,[39][40][41][42][43][44][45]48,49,51,52,[56][57][58] One comparative study, by Geisler et al, 25 reported preoperative assessment of the fistula for surgical planning. This prospective nonrandomized comparative study (N553) describes the use of phenazopyridine given preoperatively to identify fistula tracts.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…13,21,36,46,47,[53][54][55] All retrospective nonrandomized comparative studies (30 studies) and prospective nonrandomized comparative studies (5 studies) were considered high risk of bias because these studies evaluated interventions designated by surgeon preference, varied in their follow-up, provided limited information on evaluation of cure, and did not control for confounding factors. 14,[16][17][18][19][20][22][23][24][25][26][27][28][29][30][31][32][33][34][35]37,[39][40][41][42][43][44][45]48,49,51,52,[56][57][58] One comparative study, by Geisler et al, 25 reported preoperative assessment of the fistula for surgical planning. This prospective nonrandomized comparative study (N553) describes the use of phenazopyridine given preoperatively to identify fistula tracts.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluated domains included route of repair and the use of flaps, trimming, layered closure, antibiotics, fascial sling, and fibrin glue (Table 1). 13,14,[16][17][18][20][21][22][23][24][27][28][29][30][31][33][34][35][36][37][40][41][42][44][45][46][48][49][50][51][52][53][56][57][58] Seventeen studies were identified (two prospective nonrandomized comparative studies, 15 retrospective nonrandomized comparative studies) that evaluated vaginal compared with abdominal (through laparotomy) routes of vesicovaginal fistula repair (N51,143). 14,16,18,20,24,29,30,33,35,37,40,41,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations